PERUBAHAN NILAI CENTRAL CORNEAL THICKNESS SEBAGAI DETEKSI SEVERITAS RETINOPATI DIABETIKUM PADA PENDERITA DIABETES MELITUS TIPE II - Guntur Fazwat; Hendriati Hendriati; Weni Helvinda (Universitas Fort De Kock, 2021)
AbstractIntroduction : Hyperglycemia has a toxic effect on almost all cells in the body. Ocular complications due to hyperglycemia can occur in the cornea and retina. Retinal microvascular disorders in patients with type II DM are called diabetic retinopathy. Type II diabetes mellitus has a significant influence on the morphological, metabolic, physiological, and clinical aspects of the cornea that can be evaluated by measuring central corneal thickness (CCT) using Anterior Segment - Optical Coherence Tomography (AS-OCT). Morphological changes occur in corneal epithelium, epithelial basement membrane and basement, stromal and endothelial membrane complexes. CCT changes as changes in the retina of type II DM patients are chronic processes that lead to changes in the structure and biomechanics of the cornea and retina. Method: The subjects of this study consisted of 36 eyes of type II DM patients divided into 4 diabetic retinopathy groups (mild, moderate, severe NPDR and PDR) with GDS> 200mg / dl then CCT values were measured using AS-OCT. Result: CCT degrees in this study: normal 44.4%; thick (33.3%); thin (13.9%); ; very thick CCT (8.3%). There is no statistically significant relationship between the degree of CCT and severity of diabetic retinopathy. Conclusion: The CCT value of DM type II sufferers in the PDR group was higher than in the NPDR group, where there was an increase in CCT value along with an increase in severity of diabetic retinopathy, but the results were statistically not significant. CCT examination is expected to be one of the evaluations to evaluate the progression of hyperglycemic in type II DM against ocular disorders, especially cornea.Keywords: Type II diabetes mellitus, diabetic retinopathy, central corneal thickness, Anterior Segment - Optical Coherence Tomography AbstrakPendahuluan : Hiperglikemia memiliki efek toksik pada hampir semua sel dalam tubuh. Komplikasi okular akibat hiperglikemia dapat terjadi pada kornea dan retina. Gangguan mikrovaskuler retina pada penderita DM tipe II disebut retinopati diabetik. Diabetes melitus tipe II memberikan pengaruh signifikan pada aspek morfologis, metabolik, fisiologis, dan klinis kornea yang dapat dievaluasi dengan mengukur ketebalan kornea sentral atau central corneal thickness (CCT) menggunakan Anterior Segment – Optical Coherence Tomography (AS-OCT) . Perubahan morfologis terjadi pada epitel kornea, membran basal epitel dan kompleks membran basal, stroma, dan endotelium. Perubahan CCT sebagaimana perubahan pada retina pasien DM tipe II merupakan proses kronis yang berujung pada perubahan struktur dan biomekanik dari kornea dan retina. Metode: Subjek penelitian ini terdiri dari 36 mata penderita DM tipe II yang dibagi dalam 4 kelompok retinopati diabetikum (mild, moderate, severe NPDR dan PDR) dengan GDS > 200mg/dl kemudian diukur nilai CCT menggunakan AS-OCT. Hasil: Derajat CCT pada penelitian ini: normal 44,4%; thick (33,3%); thin (13,9%); very thick CCT (8,3%). Tidak terdapat hubungan yang bermakna secara statistik antara derajat CCT terhadap severitas retinopati diabetikum. Kesimpulan: Nilai CCT penderita DM tipe II kelompok PDR lebih tinggi dari pada kelompok NPDR, dimana tampak peningkatan nilai CCT seiring dengan peningkatan severitas retinopati diabetikum, namun hasil tersebut secara uji statistik tidak bermakna signifikan. Pemeriksaan CCT diharapkan menjadi salah satu penilaian untuk mengevaluasi progresifitas hiperglikemik pada penyakit DM tipe II terhadap gangguan okular, terutama korneaKata Kunci: Diabetes mellitus tipe II, retinopati diabetik, central corneal thickness, Anterior Segment – Optical Coherence Tomography